Analisia Karakter Peduli Lingkungan Pada Siswa Madrasah Ibtidaiyah Dalam Mewujudkan Sekolah Bersih Dan Sehat - Arifin, Muhammad Rijal; Arisanti, Kustiana; Mufidah, Nani Zahrotul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The character of caring for the environment is an attitude or action aimed at preventing damage to nature. The purpose of this research is to characterize environmental care for MI Tarbiyatul Islam students, as an independent madrasah accredited A which is in the cleanest category in Probolinggo district. The nature of the approach in this study was descriptive qualitative, the subjects in this study were high school students in grades 5A 5B 6A and 6B MI Tarbiyatul Islam Kandang jati kulon, Kraksaan, Probolinggo Regency with 5 students each. Collecting data with questionnaires and interview sheets. The score of the research results shows that MI Tarbiyatul Islam students have high environmental awareness. This is known from the results of questionnaires and interviews with students which contain four environmental management indicators, including: energy saving, waste management, water use and environmental management. This shows that grade 6B students have an average score of very high environmental awareness, while categories 5A, 5B and 6A also have high environmental awareness. From this it can be concluded that students of MI Tarbiyatul Islam in Probolinggo Regency show a high level of environmental awareness.